Changes in the Phenolic Composition and Antioxidant Activity of Pinotage, Cabernet Sauvignon, Chardonnay and Chenin blanc Wines During Bottle Ageing - de Beer, D.; Joubert, E.; Gelderblom, W.C.A.; Manley, M. (South African Journal of Enology and Viticulture, 2017)
The effect of bottle ageing on the antioxidant activity of Pinotage, Cabernet Sauvignon, Chardonnay and Chenin blanc wines, using the 2,2'-azino-di-(3-ethylbenzothialozine-sulphonic acid) radical cation (ABTS•+) and 2,2-diphenyl-1-picrylhydrazyl radical (DPPH0) scavenging assays, was determined. Storage at 0°C, 15°C or 30°C for a period of 12 months resulted in a significant (p ≤ 0.05) decrease in both the total antioxidant activity (TAAAnTs and TAAoPPH) and the total phenol content of the wines. The antioxidant potency of the total phenols of most of the wines, which is a ratio of antioxidant activity to the total phenol content, also decreased. The total anthocyanins in the red wines decreased significantly (p ≤ 0.05) over 12 months except for storage at 0°C, while the flavanol content of the Pinotage, Cabernet Sauvignon and Chardonnay wines increased up to nine months storage with a subsequent decrease to 12 months. The flavonol content of all the wines decreased, while only minor changes in their hydroxycinnamate content were observed during the storage period. Understanding the complexity of these reactions may provide clues for stabilising especially red wines to preserve the antioxidant activity without losing the beneficial effects of colouring and flavour development during bottle ageing.